Exercise with vibration dumb-bell enhances neuromuscular excitability measured using TMS - Fowler D. E.; Tok, M. I.; Çolakoglu, M.; Bademkiran, F.; Çolakoglu, Z. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The purpose of the study was to examine the effects of exercise without vibration and exercise with vibration (27 Hz) on the cortical silent period (CSP) and cortical motor threshold (CMT) measured using transcranial magnetic stimulation (TMS). METHODS: In 22 university athletes, a circular coil attached to a TMS stimulator was applied over the contralateral motor cortex of the target forearm. Resting cortical motor thresholds for dominant and non-dominant extremities were measured for each participant. Then, 15 biceps curls (15 flexion and 15 extension movements) were performed with the dominant arm using a single vibration dumbbell with the vibration turned off. On a different day, the same biceps curl protocol was performed with the dumbbell vibrating at 27 Hz (2 mm amplitude). A supra-threshold TMS stimulus (1.5x CMT) was delivered while participants were voluntarily contracting the flexor digitorum sublimus muscle (30% MVC grip strength) to determine cortical silent periods before and after each upper extremity exercise protocol. Cortical motor thresholds were measured at rest and after the vibration exercise protocol. RESULTS: All subjects completed the study protocol as designed. After TMS, the CSP in the dominant (exercised) extremities increased after exercise without vibration from a resting (pre-exercise) mean of 57.3 ms to 70.4 ms (P<0.05) and after exercise with vibration, the CSP decreased to a mean of 49.4 ms (P<0.02). The CSP in the non-dominant (unexercised) extremities decreased from resting values of 75.6 ms to 69.3 ms (P=0.935) after the exercise-only protocol and decreased to 49.4 ms (P<0.01) after the vibration exercise protocol. The cortical motor threshold in exercised extremities decreased from a resting mean of 41.4 mV to a postvibration exercise mean of 38.6 mV (P<0.01). In non-exercised extremities, the CMT also decreased, from mean of 43.5 mV to 39.9 mV after the vibration-exercise (P<0.01). CONCLUSION: Vibration exercise enhances bilateral corticospinal excitability, as demonstrated by a shortened cortical silent period and lower cortical motor threshold in both exercised and non-exercised extremities.